Nrf2-BDNF-TrkB pathway contributes to cortical hemorrhage-induced depression, but not sex differences. Issue 12 (December 2021) - Ren, Honglei; Han, Ranran; Liu, Xi; Wang, Limin; Koehler, Raymond C; Wang, Jian
Post-stroke depression, observed in 30-50% of stroke patients, negatively affects quality of life and mortality. The pathogenesis of post-stroke depression is complex, but heightened reactive oxygen species production and inflammation might be two key factors. We have reported that intracerebral hemorrhage (ICH) in cerebral cortex produces depression-like behavior in young male mice. Here, we found that mice lacking nuclear factor erythroid-derived 2-related factor 2 (Nrf2), a transcription factor that upregulates antioxidant proteins and trophic factors such as brain-derived neurotrophic factor (BDNF), had more severe depression-like behavior than wild-type mice at days 21 to 28 after cortical ICH (c-ICH). Moreover, the expression of Nrf2, heme oxygenase-1, BDNF, and TrkB were significantly decreased in wild-type mice after c-ICH. Interestingly, TP-500 (2 mg/kg), a potent Nrf2 inducer, decreased the inflammatory response and reactive oxygen species production on day 28 after c-ICH and improved depression-like behaviors. TrkB receptor antagonist ANA-12 abolished this anti-depression effect. Depression was more severe in female than in male wild-type mice after ICH, but TP-500 improved depression-like behavior in females. These results suggest that downregulation of Nrf2-BDNF-TrkB signaling contributes to development of post-stroke depression, and that Nrf2 inducer TP-500 might improve depression after c-ICH.